Building maintenance management - Chanter, Barrie; Swallow, Peter (New Delhi Blackwell Publishing/Wiley India Pvt. Ltd., 2007)
Chanter and Swallow offer a comprehensive profile of the many aspects of property maintenance. This text has been updated throughout with current legislation, contractual forms, and government policy, and includes a new chapter on facilities management.
Includes bibliographical references and index.
Keywords: Buildings -- Maintenance -- Management